Analysis of The Influence of Quality Control and Assurance on Management Resilience in Educational Organizations in Carrying Out Organizational Changes and Transformations - Vivid Violin; Darwis Darwis; Haniwijaya Pahlawansah; Syeh Assery; Isep Nendri Rostiana (Departement of Mathematics Education, 2024)
This study aims to identify factors that influence management capabilities, especially in educational institutions, to adapt and transform in the digital era. This study uses a mixed method between quantitative and qualitative. This study involved 100 respondents and used a questionnaire as the main instrument for data collection. The results of the study indicate that the challenges faced by management in higher education require focus and improvement in governance. Universities that have been established for a long time encounter obstacles in implementing the effectiveness of the chain of command and streamlining the communication hierarchy. Universities face significant challenges in terms of human resource management and how to build good leadership quality. Several factors such as quality assurance systems and motivation also play an important role in influencing the managerial quality of educational institutions. The difference between universities that implement a quality assurance system and those that do not show that universities that do not implement a quality management system focus more on human management, while universities that implement a quality assurance system focus on matters related to administration